Necroptosis microenvironment directs lineage commitment in liver cancer - Seehawer, Marco; Heinzmann, Florian; D’Artista, Luana; Harbig, Jule; Roux, Pierre-François; Hoenicke, Lisa; Dang, Hien; Klotz, Sabrina; Robinson, Lucas; Doré, Grégory; Rozenblum, Nir; Kang, Tae-Won; et al. (Nature, 2018)
The tumour microenvironment determines which type of liver cancer develops, with transformed hepatocytes giving rise to intrahepatic cholangiocarcinoma or hepatocellular carcinoma depending or whether they are surrounded by cells undergoing necroptosis or apoptosis.
Gesehen am 04.09.2019